Efektifitas Program PHBS (Perilaku Hidup Bersih dan Sehat) ditinjau dari Kebutuhan Masyarakat Pada Saat Pandemic Covid-19 - Linda Astriani; Karina Vianka Irawan; Munifah Bahfen (Edumedia Solution, 2022)
The purpose of community service in this KKN activity is to find out the effectiveness of the PHBS program that is recommended to the community to be applied in daily life in order to keep oneself healthy in the midst of the threat of COVID-19 transmission. The PHBS program is specifically designed to answer the needs of residents during this pandemic with the aim of increasing public understanding and changing the pattern of activities that people usually do during this pandemic. The community response related to the PHBS program is that this program can help implement PHBS very well with a percentage of 100%, this program provides a clear picture of the implementation of PHBS with a 100% response, and the PHBS program in its application to the community has received a response of 77.8% of the community stating